2022
DOI: 10.1371/journal.ppat.1010167
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhimurium chitinases modulate the intestinal glycome and promote small intestinal invasion

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) is one of the leading causes of food-borne illnesses worldwide. To colonize the gastrointestinal tract, S. Typhimurium produces multiple virulence factors that facilitate cellular invasion. Chitinases have been recently emerging as virulence factors for various pathogenic bacterial species, and the S. Typhimurium genome contains two annotated chitinases: STM0018 (chiA) and STM0233. However, the role of these chitinases during S. Typhimurium pathogenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 61 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…Typhimurium-caused intestinal damage, as evidenced by the reduced colon shortening and colon and ileum histological damage. In agreement with the previous study ( 24 ), we confirmed that the administration of HNa decreased the proinflammatory cytokines such as myeloperoxidase (MPO), interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukin-2 (IL-2) in both the serum and colon of S . Typhimurium-infected mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Typhimurium-caused intestinal damage, as evidenced by the reduced colon shortening and colon and ileum histological damage. In agreement with the previous study ( 24 ), we confirmed that the administration of HNa decreased the proinflammatory cytokines such as myeloperoxidase (MPO), interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukin-2 (IL-2) in both the serum and colon of S . Typhimurium-infected mice.…”
Section: Discussionsupporting
confidence: 92%
“…Typhimurium is one of the main causes of foodborne illnesses worldwide ( 23 ). The antibacterial property of HNa has been widely reported ( 24 ). However, the antibacterial effect of HNa on S .…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes within the GH18 family are primarily recognized for their roles in chitin depolymerization but have also been reported to hydrolyze fragments of peptidoglycan, Nod-factors, LacdiNAc, glycans from IgG and IgA, carbohydrates present on mammalian glycoproteins, and mucin extracts, illustrating the functional diversity of these enzymes ( 18 , 66 74 ). In the context of chitin metabolism, PA is unable to grow on chitin particles ( 11 ), exhibits delayed growth on GlcNAc ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is noteworthy that other GH18 family enzymes have been shown to have activity toward non-chitin substrates, such as ChiA from S. Typhimurium and L. monocytogenes (which cleaves LacdiNAc, a disaccharide motif common in mucins), ChiA from L. pneumophila (associated with mucin hydrolysis), and a recent study showing ChiA of S . Typhimurium (altering the N- glycome profile of gut epithelial cells) ( 18 , 66 , 67 ) (the structures of ChiC and these enzymes are shown in Fig. 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time qPCR was performed using iTaq Universal SYBR Green Supermix with CFX384 Real-Time System (Bio-Rad). Primers and cycling conditions were derived from Devlin et al, 2022 55 (Table S10).…”
Section: Rt-qpcrmentioning
confidence: 99%